Coevolutionary analysis of the Philopteroides Mey, 2004 (Phthiraptera: Ischnocera) parasitizing bulbuls (Passeriformes: Pycnonotidae) - Ren, Mengjiao; Gustafsson, Daniel R.; Tian, Chunpo; Grossi, Alexandra A.; Liu, Zhixiao; Zou, Fasheng (Frontiers in Ecology and Evolution, 2023)
Introduction Avian head lice comprise a diverse group of distantly related genera of lice that exhibit a strongly convergent morphology. Due to their lack of free-living stages, their strong morphological adaptations to living on the host’s head, and the limited opportunities for transfer between hosts during mating or nesting, the lateral transmission of head lice between non-conspecific hosts may be presumed to be restricted. Despite this, many species of head lice are ostensibly host generalists. We here examine lice of the head louse genus Philopteroides Mey, 2004, from bulbuls (Passeriformes: Pycnonotidae). Methods We use two different methods, ParaFit and Jane, to get insights on the co-evolutionary history of Philopteroides species and their bulbul hosts. Jane was run with a variation of event costs. Results Our phylogenetic analysis indicate that several morphologically cryptic species can be found in this group, most of which appear to be host specific. However, co-phylogenetic analyses indicate that host-switching has been common in the history of these lice, and co-speciation events have been rarer than expected. Moreover, lowest-cost co-evolutionary reconstructions under a variety of event costs are indistinguishable from random. An expanded dataset with more Philopterus-complex lice was found to be evenly balanced between host-switching and co-speciation events. Discussion The transfer of avian head lice between host species is poorly understood, but evidently fairly common. Several potential routes are discussed, but direct evidence is missing. Potentially, the presence of multiple bulbul species at fruiting trees may be an important factor in this transfer. However, such transfer routes also do not explain why Philopteroides lice on bulbuls appear to be distinct from those of other hosts. Moreover, as many of the species recovered in our analysis are morphologically indistinguishable, cryptic speciation appears to be common in this group.